Penerapan Project-based Learning Model pada Mata Pelajaran Instalasi Penerangan Listrik - Taali Taali; Suci Ananda (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study was conducted to determine the effect of the application of the Project-Based Learning Model on the subject of Electrical Lighting Installation at SMK Negeri 1 Sumatera Barat. his study uses experimental research methods. The research design used is a pre-experimental one-group pretest-posttest design. This design involves one group being given a pretest (O1), given treatment (X), and given a posttest (O2). The research subjects were students of class XI TITL 2 SMK Negeri 1 Sumatera Barat for the academic year 2023/2024. The first measurement was carried out before the subjects were given treatment and the second measurement was after the subjects were treated. The results showed that the application of the Project-Based Learning Model in the class XI TITL 2 Electrical Lighting Installation subject at SMK Negeri 1 Sumatera Barat can improve student learning outcomes. These results can be seen from the realm of knowledge, namely the results of the pretest and posttest which were analyzed using the N-Gain Score formula into the moderate category and using completeness learning outcomes increase from medium to very high categories. With the acquisition of these data, it can be concluded that the application of the Project-Based Learning Model improves student learning outcomes in the XI TITL 2 students is greatly improved in the Electrical Lighting Installation subject.